2021
DOI: 10.1111/lam.13516
|View full text |Cite
|
Sign up to set email alerts
|

Targeted amplification and MinION nanopore sequencing of key azole and echinocandin resistance determinants of clinically relevant Candida spp. from blood culture bottles

Abstract: The objective of the study was to evaluate the use of targeted multiplex Nanopore MinION amplicon re‐sequencing of key Candida spp. from blood culture bottles to identify azole and echinocandin resistance associated SNPs. Targeted PCR amplification of azole (ERG11 and ERG3) and echinocandin (FKS) resistance‐associated loci was performed on positive blood culture media. Sequencing was performed using MinION nanopore device with R9.4.1 Flow Cells. Twenty‐eight spiked blood cultures (ATCC strains and clinical iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Whole genome sequence Illumina reads of C. albicans were downloaded from NCBI for four studies: Hirakawa et al 2015 50 (21 genomes), Chew et al 51 2021 (14 genomes), Szarvas et al 2021 53 (30 genomes), and Gong et al 2023 52 (370 genomes). Reads were checked for quality with fastqc v0.12 100 , trimmed with Trimmomatic v0.39 101 , and mapped to the A haplotype of C. albicans SC5314 genome assembly A22-s07-m01-r183 (Candida Genome Database, accessed in August 2023) using bwa-mem2 v2.2.1 102 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole genome sequence Illumina reads of C. albicans were downloaded from NCBI for four studies: Hirakawa et al 2015 50 (21 genomes), Chew et al 51 2021 (14 genomes), Szarvas et al 2021 53 (30 genomes), and Gong et al 2023 52 (370 genomes). Reads were checked for quality with fastqc v0.12 100 , trimmed with Trimmomatic v0.39 101 , and mapped to the A haplotype of C. albicans SC5314 genome assembly A22-s07-m01-r183 (Candida Genome Database, accessed in August 2023) using bwa-mem2 v2.2.1 102 .…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate if the deleterious effects we measured in S. cerevisiae can be generalized to natural C. albicans populations, we analyzed 435 genomes from four studies that were publicly available [50][51][52][53] . Although polymorphisms are limited because we study a single gene, we identified variable amino acid substitutions overlapping the genomic dataset and our DMS library.…”
Section: Impact Of Mutations On the Function Of Erg11mentioning
confidence: 99%
“…Hence, detection of genes known to confer antifungal resistance or novel resistance mutations is reliant on DNA sequencing. Whilst Sanger sequencing may suffice where a limited number of genes are being analysed, WGS provides a genome-wide view of gene mutations and is also able to detect new combinations of mutations that might otherwise be missed with targeted DNA sequencing [130][131][132]. Even for echinocandin resistance where clinical utility is best understood, no commercial methods are currently available.…”
Section: Candida and Candida-like Organismsmentioning
confidence: 99%
“…This approach has provided evidence about mutations, with no known previous association with phenotypic drug resistance of the ERG and FKS genes in Candida spp. [128].…”
Section: Next Generation Sequencing (Ngs)mentioning
confidence: 99%